Recent advances in stimuli-responsive polymers for sensing and actuation. Issue 2 (29th January 2021) - Hu, Liang; Shu, Tong; Wan, Yu; Fang, Changhao; Gao, Feng; Serpe, Michael J.
Abstract : Stimuli-responsive polymers (SRPs) are capable of changing their solubility, conformation, and volume in response to external stimuli. Here, we detail how SRPs can be used for sensing and actuation, and focus on the response mechanism. Abstract : Stimuli-responsive polymers (SRPs) are capable of changing their solubility, conformation, and volume in response to external stimuli. By understanding the nature of the responsivity and the synthetic challenges, new SRPs can be synthesized with enhanced responsivities at scales that will allow their use in the real world. In this review, many fundamental concepts and recent advances in SRPs for sensing and actuation are presented. A variety of sensors that can respond to physiologically relevant species and stimuli are reviewed, including temperature/pH, proteins, glucose and ions. The review also includes examples of the use of SRPs for artificial muscles, soft robots, cell culture, and drug delivery.